Policy Brief on Ensuring Safe Vegetable Production amid Heavy Metal Risks Free from Wastewater Irrigation in Punjab, Pakistan - Muhammad Mazhar Iqbal*; Tayyaba Naz; Iqra Ghafoor; Fraza Ijaz; Saiqah Toor; Syed Ali Zulqadar; Hafiz Abu Bakar Amin; Ahmad Mustafa; Kafeel Ahmad; Abdul Rehman; Muhammad Usman Ghazanfar; Salman Ahmad; et al. (Social Science Review Archives, 2025)
The untreated wastewater irrigation in producing vegetables from the peri-urban areas of Punjab, Pakistan, poses enormous health risks because the wastewater, particularly the industrial wastewater, is a source of heavy metals that cumulate in vegetables. This policy brief accentuates the contamination of wastewater irrigated vegetables with heavy metals and gives recommendations on safe vegetable production based on recent studies. This policy brief calls for the need to have strict regulation and monitoring of irrigation practices based on wastewater for sustainable agriculture and public health assurance.